Rubber sealing material and preparation method thereof
Through the combination of fluorosilicone rubber, polar rubber blending, graphene, filler and vulcanization treatment, the problem of poor low-temperature and oil resistance of rubber sealing materials under low temperature conditions is solved, and its sealing performance in extremely cold environments is improved.
Patent Information
- Application Number
- CN202411356637.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-10
AI Technical Summary
The existing rubber sealing materials have poor low temperature and oil resistance under low temperature conditions, and cannot meet the sealing requirements in extremely cold environments, resulting in safety risks in transformer equipment operation.
Fluorosilicone rubber and polar rubber blend are used as rubber matrix, and a bridge structure is formed through graphene and filler, combining sulfur vulcanization and peroxide dual vulcanization system to form a polysulfide bond and carbon-carbon single-bonded vulcanization structure to enhance rubber Mechanical properties and low temperature and oil resistance.
It significantly improves the mechanical strength, low temperature and oil resistance of rubber sealing materials, so that they can withstand insulating oil for a long time under low cold conditions without being easily deformed, and has excellent sealing performance.
Smart Images

Figure CN119286263A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber sealing materials, and in particular to a rubber sealing material and a preparation method thereof. Background Art
[0002] With the accelerated construction of new power systems, the requirements for the reliability of substation equipment have become increasingly prominent. The electrical performance of oil-filled electrical equipment such as large transformers has been synchronized with that of foreign countries, but seals frequently fail due to aging in key sealing positions, and insulating oil leakage poses a great safety hazard to the operation of electrical equipment. Common seals for power transformers include O-ring seals, O-ring sealing strips, rubber gaskets, and some special-shaped seals. Among them, rubber sealing materials have excellent resilience and oil resistance and are widely used in transformer equipment.
[0003] However, the performance and service life of rubber materials are easily affected by the service environment conditions. Under low temperature conditions, the molecular motion of vulcanized rubber is weakened, resulting in a significant decrease in entropy elasticity, an increase in hardness, modulus and intramolecular friction, and the rubber material changes from a low modulus high elasticity to a high modulus glass state. When the temperature is lower than the glass transition temperature, the rubber material eventually loses its high elasticity and loses its working ability. In order to improve the sealing performance of transformer products in high-cold areas, it is urgent to develop rubber materials with excellent low temperature and oil resistance to improve the service reliability of transformer equipment. Summary of the invention
[0004] The purpose of the present invention is to solve the technical problem that the rubber sealing material in the prior art has poor low temperature and oil resistance and cannot meet the sealing requirements in an extremely cold environment.
[0005] The purpose of the present invention is to adopt the following technical solutions to achieve:
[0006] A rubber sealing material comprises the following raw materials, measured by weight: 50-80 parts of fluorosilicone rubber, 20-50 parts of polar rubber, 2-10 parts of graphene, 30-60 parts of filler, 3-20 parts of vulcanization treatment agent and 7.1-31 parts of auxiliary agent.
[0007] Preferably, the fluorosilicone rubber contains 0.1-5% vinyl in molar mass, and the molecular weight of the fluorosilicone rubber is 300,000-600,000. Vinyl is an olefin group with the characteristics of high unsaturation and strong reactivity. After the fluorosilicone rubber is copolymerized with vinyl siloxane, vinyl is introduced into the molecular chain, which can not only improve the physical and mechanical properties of the fluorosilicone rubber such as resistance to hydrogen solvents and oil resistance, but also improve the vulcanization performance of the rubber. If the vinyl content is too low, the crosslinking density of the fluorosilicone rubber will decrease, the hardness will be low, and the tear strength will be low. If the vinyl content is too high, the hardness of the fluorosilicone rubber will become larger and brittle, and the aging resistance will decrease. Therefore, the more suitable molar content range of vinyl is 0.1-5%; and the fluorosilicone rubber with a molecular weight in the range of 300,000-600,000 has good low-temperature flexibility, low brittle temperature, and is relatively stable at low temperatures.
[0008] Preferably, the polar rubber is one or more of nitrile rubber with 20-50% acrylonitrile mass percentage, hydrogenated nitrile rubber with 20-40% acrylonitrile mass percentage and chloroprene rubber. Nitrile rubber and hydrogenated nitrile rubber are copolymers formed by polymerization of acrylonitrile and butadiene monomers, have good oil resistance, strong adhesion, and have a low expansion rate in oil substances. The more acrylonitrile content, the better the oil resistance, but the cold resistance decreases accordingly. Therefore, the present invention preferably uses nitrile rubber with 20-50% acrylonitrile mass percentage and hydrogenated nitrile rubber with 20-40% acrylonitrile mass percentage, which take into account both high oil resistance and low temperature resistance.
[0009] Preferably, the vertical thickness of the graphene is 1-5 nm and the lateral thickness is 0.5-5 m. Graphene provides a honeycomb lattice structure for the rubber matrix as a bridging medium (carrier), greatly improving the compatibility between polar rubber and non-polar rubber, and improving the mechanical properties of rubber. The smaller the lattice gap of graphene, the stronger the binding force between rubber molecules and the higher the mechanical properties.
[0010] Preferably, the filler is one or more of carbon black and silicon dioxide. Carbon black includes carbon black N330, carbon black N550, carbon black N660, carbon black N990 and the like.
[0011] Preferably, the filler is spherical and is embedded with the graphene sheet structure to form an interlaced grid structure. The filler can enhance the strength, hardness and wear resistance of the rubber. The interlaced grid structure formed by the graphene and the filler can make the rubber matrix molecules more tightly bound and the structure more solid, further enhancing the mechanical properties of the rubber. At the same time, the interlaced grid structure can also improve the barrier performance of the rubber matrix to the insulating oil medium, further improving the oil resistance.
[0012] Preferably, the vulcanization treatment agent includes the following components in parts by mass:
[0013] 0.5-3 parts of zinc oxide, 0.5-3 parts of stearic acid, 0.5-3 parts of co-vulcanizing agent, 0.5-5 parts of vulcanization accelerator, 0.5-3 parts of sulfur vulcanizing agent and 0.5-3 parts of peroxide vulcanizing agent.
[0014] Preferably, the co-vulcanizing agent is one or more of triallyl isocyanurate, N,N'-m-phenylene bismaleimide, and trimethylolpropane triacrylate.
[0015] Preferably, the vulcanization accelerator is one or more of accelerator TMTM, accelerator TMTD, accelerator M, accelerator DM, accelerator CZ, and accelerator NS.
[0016] Preferably, the peroxide curing agent is one or more of 1,3-di-tert-butylperoxyisopropylbenzene, diisopropylbenzene peroxide, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.
[0017] The activator, the co-vulcanizing agent, the vulcanization accelerator and the vulcanizing agent together constitute the rubber vulcanization system. The present invention adopts sulfur vulcanizing agent and peroxide vulcanizing agent as vulcanizing agents, introduces a sulfur vulcanization and peroxide dual vulcanization system into the rubber vulcanization system, can form a polysulfide bond vulcanization structure in the rubber matrix, and also forms a high temperature resistant and stable carbon-carbon single bond vulcanization structure, under the action of the double chemical cross-linking bonds, improves the low temperature and oil resistance of the rubber material and the material anti-aging ability.
[0018] It can be understood that by blending low-temperature resistant fluorosilicone rubber with oil-resistant polar rubber as the rubber matrix, and using the grid structure formed by the interlacing of lattice-like lamellar graphene and spherical fillers as the carrier, and at the same time using a double-crosslinked vulcanization system constructed by sulfur vulcanization and peroxide, it is possible to synergistically promote the improvement of the high oil resistance and low-temperature resistance of the rubber material.
[0019] Preferably, the auxiliary agent includes the following components in parts by mass:
[0020] 5 to 20 parts of low temperature resistant plasticizer, 0.1 to 5 parts of modifier and 2 to 6 parts of antioxidant.
[0021] Preferably, the low temperature plasticizer is one or more of dioctyl adipate, diisooctyl sebacate, diisononyl adipate, liquid nitrile rubber, liquid ethylene propylene rubber, and liquid fluorosilicone rubber. Rubber plasticizers are also called softeners, which can reduce the force between rubber molecules, enhance the plasticity and fluidity of rubber, and facilitate molding operations such as calendering and extrusion. The use of low temperature plasticizers can also enhance the cold resistance and low temperature resistance of rubber materials.
[0022] Preferably, the modifier is one or more of 3-mercaptopropylmethyldiethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-mercaptopropyltrimethoxysilane. Both graphene and lamellar fillers can be surface-modified by the modifier, which can improve their dispersibility in the rubber matrix, enhance the bonding force between the rubber matrix molecules, and at the same time, improve the barrier performance of the rubber matrix to the insulating oil medium, and improve the mechanical properties and oil resistance.
[0023] Preferably, the antioxidant is one or more of antioxidant RD, antioxidant 4010NA, antioxidant 2246, and antioxidant MB. The antioxidant mainly delays the aging process of rubber and prolongs the service life of rubber.
[0024] Based on the same inventive concept, the present invention also provides a method for preparing the rubber sealing material as described above, comprising the following steps:
[0025] Rubber matrix mixing: mixing fluorosilicone rubber, polar rubber and graphene at 120-150° C. for 5-10 minutes to obtain a rubber matrix mixed rubber;
[0026] One-stage mixing: adding fillers and additives to the rubber matrix mixed rubber, mixing at 80-100° C. for 5-10 minutes to obtain a one-stage mixed rubber;
[0027] Second stage mixing: adding a vulcanizing agent to the first stage mixed rubber, and performing second stage mixing at 50 to 80° C. for 3 to 5 minutes to prepare the rubber sealing material.
[0028] Preferably, before the rubber matrix is mixed, the following steps are further included:
[0029] Placing graphene powder in a dispersion, adding a modifier, carrying out a modification reaction at 100 to 150° C. for 2 to 10 hours, and obtaining a modified graphene wet powder after suction filtration;
[0030] The graphene in the rubber matrix mixing process is modified graphene.
[0031] Preferably, the mass content of the modifier is 0.1 to 2 times that of the graphene.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The present invention provides a rubber sealing material, which includes the following raw materials by mass: 50-80 parts of fluorosilicone rubber, 20-50 parts of polar rubber, 2-10 parts of graphene, 30-60 parts of filler, 3-20 parts of vulcanization treatment agent and 7.1-31 parts of auxiliary agent. The present invention introduces fluorosilicone rubber with excellent low temperature resistance and oil resistance, and polar rubber with excellent oil resistance, and introduces graphene into the blending system to form a bridge structure between the fluorosilicone rubber and the polar rubber, improve the compatibility between the rubber matrix, and then combine the reinforcing effect of the filler to synergistically improve the mechanical strength, low temperature resistance and oil resistance of the rubber material, so that it can withstand long-term immersion in insulating oil under low-cold conditions, and is not prone to deformation caused by segment slippage, and has excellent sealing performance.
[0034] The present invention uses a vulcanization agent as a rubber vulcanization system to plastically shape the rubber. The vulcanization agent adopts a dual vulcanization system of sulfur vulcanization and peroxide, which can form a polysulfide bond vulcanization structure in the rubber matrix, and also form a high-temperature resistant and stable carbon-carbon single bond vulcanization structure. Under the action of the double chemical cross-linking bonds, the low-temperature and oil resistance and the anti-aging ability of the rubber material are improved.
[0035] The present invention activates the vulcanization system by adding an auxiliary agent, improves the crosslinking density and aging resistance of the vulcanized rubber, and adds a modifier to the auxiliary agent to perform surface modification on graphene, thereby improving its dispersibility in the rubber matrix and enhancing the bonding force between rubber matrix molecules. At the same time, it can also improve the barrier performance of the rubber matrix to the insulating oil medium, and improve the mechanical properties and oil resistance.
[0036] The present invention uses a high-temperature mixing process to form a bridge structure of graphene between fluorosilicone rubber and polar rubber, thereby improving the compatibility between the rubber matrix.
[0037] The present invention uniformly disperses the filler into the rubber matrix through a high-temperature mixing process, thereby synergistically improving the mechanical strength, low-temperature resistance and oil resistance of the rubber matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The figure is a schematic flow chart of an embodiment of a method for preparing a rubber sealing material of the present invention. DETAILED DESCRIPTION
[0039] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0040] Example 1
[0041] The rubber sealing material of this embodiment includes, by mass, 50 parts of fluorosilicone rubber, 50 parts of nitrile rubber, 2 parts of graphene, 1 part of 3-mercaptopropylmethyldiethoxysilane, 30 parts of carbon black N330, 2 parts of sulfur, 3 parts of 1,3-di-tert-butylperoxyisopropylbenzene, 1.2 parts of triallyl isocyanurate, 2.5 parts of accelerator TMTM, 5 parts of dioctyl adipate, 1.5 parts of zinc oxide, 2 parts of stearic acid, and 4 parts of antioxidant 4010NA. Among them, the molecular weight of fluorosilicone rubber is 500,000, and the molar content of vinyl is 1%; the mass percentage of acrylonitrile in nitrile rubber is 50%; the vertical dimension of graphene is 1nm and the lateral dimension is 0.5m.
[0042] Rubber sealing materials have excellent resilience and oil resistance and are widely used in transformer equipment. However, under low temperature conditions, due to the weakening of molecular motion of vulcanized rubber, the rubber material changes from low modulus high elasticity to high modulus glass state. When the temperature is lower than the glass transition temperature, the rubber material loses its high elasticity and working ability. Traditional rubber sealing materials are usually improved by blending and modifying cis-1,4-butadiene rubber, styrene-butadiene rubber and fluorosilicone rubber to improve the low temperature performance of rubber sealing gaskets. However, since transformer rubber sealing materials need to be immersed in insulating oil for a long time, the non-polar rubber components in the rubber are prone to swelling and cannot meet the transformer sealing requirements.
[0043] The quality of oil resistance is related to the polar units in the molecular structure of rubber materials, while low temperature resistance is related to the non-polar units in rubber materials. The polarity difference of the rubber matrix will cause the material to form microphase separation at the microscopic level, so there is a contradiction between the low temperature resistance and oil resistance of rubber materials. In order to achieve a balance between low temperature resistance and oil resistance, traditional rubber is mainly based on mixed polyurethane, and a small amount of nitrile rubber or chloroether rubber is used. The balance between low temperature resistance and oil resistance is achieved by optimizing various components of rubber, and the glass transition temperature Tg can reach below -40C. However, although the service temperature range of the material can be controlled by designing the ratio of soft and hard segments, the hard segment structure in the mixed polyurethane is prone to slippage between segments under long-term sealing, resulting in permanent deformation and affecting the sealing performance.
[0044] Therefore, the selection of rubber matrix for low-temperature resistant rubber sealing materials is particularly important, and the compatibility of different rubber matrices is also the key to ensuring the performance of rubber materials.
[0045] Fluorosilicone rubber, also known as γ-trifluoropropylmethylpolysiloxane, is a linear polymer composed of soft Si-O as the main chain. It has low-temperature softness and a brittle temperature as low as -89°C. Its low-temperature properties are better than those of fluororubber with CC as the main chain, and it maintains the excellent properties of organic silicone materials such as heat resistance, cold resistance, high voltage resistance, and weather aging resistance. Due to the introduction of fluorine-containing groups, fluorine atoms have a great electron-withdrawing effect. In addition, the bond length of the CF bond is relatively short, which can form a good shielding effect on the CC bond and has good resistance to non-polar substances. This makes fluorosilicone rubber have the excellent hydrogen solvent resistance, oil resistance, and lower surface energy properties of organic fluorine materials. Therefore, while maintaining a series of excellent properties of silicone rubber such as heat resistance, cold resistance, compression recovery, resilience, electrical properties, and demolding, fluorosilicone rubber also has the oil resistance and solvent resistance of fluororubber. Because fluorosilicone rubber has excellent resistance to hydrogen solvents, oil resistance and low temperature resistance, its expansion rate in oil substances is low in low temperature environments, and it can withstand long-term immersion in insulating oil under low-cold conditions.
[0046] Polar rubber refers to rubber containing polar groups in its molecular chain, usually nitrile rubber, chloroprene rubber, etc. Polar rubber is more resistant to hydrocarbon solvents and oils than non-polar rubber. It has a lower expansion rate in oil substances and can withstand long-term immersion in insulating oil.
[0047] Graphene is an allotrope of carbon, with carbon atoms arranged in sp 2 Hybrid bonding forms a single-layer hexagonal honeycomb lattice structure, which is one of the strongest materials known. It also has good toughness. The theoretical Young's modulus of graphene is 1.0TPa, the inherent tensile strength is 130GPa, and it is not easy to deform in low temperature environments. Reduced graphene modified by hydrogen plasma also has very good strength, with an average modulus of up to 0.25TPa.
[0048] The present invention uses fluorosilicone rubber with excellent cold and oil resistance and polar rubber with excellent oil resistance as the mixed rubber matrix, which can greatly improve the low temperature and oil resistance of the rubber sealing material. At the same time, the rubber matrix used in the present invention has a low oil expansion rate and does not contain non-polar rubber, avoiding the swelling phenomenon caused by the non-polar rubber component, and can withstand long-term immersion in insulating oil under low-cold conditions. The present invention introduces graphene to form an overseas structure between the fluorosilicone rubber and the polar rubber, improves the compatibility between the rubber matrix, and combines the reinforcing effect of the filler to improve the overall mechanical strength of the rubber matrix, avoid deformation caused by slippage between molecular segments under long-term sealing, and improve the sealing performance of the rubber material.
[0049] Therefore, the present invention introduces fluorosilicone rubber with excellent low-temperature resistance and oil resistance, and polar rubber with excellent oil resistance, and introduces graphene into the blending system to form a bridging structure between the fluorosilicone rubber and the polar rubber, thereby improving the compatibility between the rubber matrices. Combined with the reinforcing effect of the filler, the mechanical strength, low-temperature resistance and oil resistance of the rubber material are synergistically improved, so that the rubber material can withstand long-term immersion in insulating oil under low-cold conditions, is not prone to deformation caused by segment slippage, and has excellent sealing performance.
[0050] Rubber materials usually need to be plastically formed by vulcanization treatment. The present invention uses a vulcanization agent as a rubber vulcanization system to plastically form the rubber, and activates the vulcanization system by adding an auxiliary agent to improve the crosslinking density and aging resistance of the vulcanized rubber.
[0051] Figure 1 A schematic flow chart of the preparation method of the rubber sealing material of the present invention is given. Figure 1 This embodiment provides a specific method for preparing a rubber sealing material, and the steps are as follows:
[0052] Step S1: modifying graphene: dispersing graphene powder in an ethanol / water dispersion, then adding 3-mercaptopropylmethyldiethoxysilane to the dispersion, subjecting the dispersion to a modification reaction in a high-pressure reactor at a temperature of 100° C. for 10 hours, and filtering and washing the reaction liquid in the high-pressure reactor three times using a suction filtration device to obtain modified graphene powder;
[0053] Rubber matrix mixing and modification: the internal mixer was pre-adjusted to a temperature of 80°C, fluorosilicone rubber, nitrile rubber, modified graphene powder and antioxidant 4010NA were added in sequence, the mixing temperature was increased to 150°C, and mixing was performed for 5 minutes to prepare a rubber matrix mixed rubber;
[0054] Step S2: one-stage mixing: the modified rubber mixture is put into an internal mixer, and carbon black N330, dioctyl adipate, zinc oxide, and stearic acid are added in sequence, the internal mixing temperature is set to 80° C., and mixing is performed for 10 minutes to prepare a one-stage rubber mixture;
[0055] Step S3: two-stage rubber mixing: put the above-mentioned first-stage rubber mixing into an internal mixer, and add sulfur, 1,3-di-tert-butyl peroxyisopropylbenzene, triallyl isocyanurate, and accelerator TMTM in sequence, set the internal mixing temperature to 50°C, mix for 5 minutes, prepare the second-stage rubber mixing, and let it stand for 48 hours to prepare the rubber sealing material of this embodiment.
[0056] The preparation method of the rubber sealing material of the present invention adopts a high-temperature mixing process to form a bridge structure of graphene between fluorosilicone rubber and polar rubber, thereby improving the compatibility between the rubber matrix. At the same time, the filler is evenly dispersed into the rubber matrix through the high-temperature mixing process, thereby synergistically improving the mechanical strength, low-temperature resistance and oil resistance of the rubber matrix.
[0057] Example 2
[0058] The rubber sealing material of this embodiment includes, by mass, 80 parts of fluorosilicone rubber, 20 parts of nitrile rubber, 5 parts of graphene, 5 parts of 3-mercaptopropyltrimethoxysilane, 50 parts of carbon black N330, 10 parts of silicon dioxide, 3 parts of sulfur, 2.5 parts of diisopropyl peroxide, 1.5 parts of N,N'-m-phenylene bismaleimide, 1.5 parts of accelerator TMTD, 5 parts of diisooctyl sebacate, 3 parts of zinc oxide, 3 parts of stearic acid, and 3 parts of antioxidant RD. Among them, the molecular weight of fluorosilicone rubber is 300,000, and the molar content of vinyl is 1%; the mass percentage of acrylonitrile in nitrile rubber is 20%; the vertical dimension of graphene is 1nm and the lateral dimension is 0.5m.
[0059] The preparation method of the rubber sealing material in this embodiment is different from that in Embodiment 1 in that:
[0060] In step S1, the graphene modification reaction temperature is 120° C., and the reaction time is 5 h; the internal mixer is pre-adjusted to a temperature of 70° C., and the subsequent internal mixing temperature is 120° C., and the mixing time is 8 min, to prepare a modified rubber mixture;
[0061] In step S2, the mixing temperature of the first stage mixing is 100° C., the mixing time is 5 min, and a first stage mixed rubber is prepared.
[0062] In step S3, the second stage mixing temperature is 60°C, the mixing time is 4 minutes, and the mixture is left to stand for 48 hours, thereby preparing the rubber sealing material of this embodiment.
[0063] Example 3
[0064] The rubber sealing material of this embodiment includes, by mass, 70 parts of fluorosilicone rubber, 30 parts of hydrogenated nitrile rubber, 3 parts of graphene, 5 parts of 3-mercaptopropyltrimethoxysilane, 40 parts of carbon black N660, 10 parts of silicon dioxide, 2.5 parts of sulfur, 2.5 parts of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 2 parts of trimethylolpropane triacrylate, 3.5 parts of accelerator M, 15 parts of diisooctyl sebacate, 2.5 parts of zinc oxide, 2.8 parts of stearic acid, and 2 parts of antioxidant MB. Among them, the molecular weight of fluorosilicone rubber is 500,000, and the molar content of vinyl is 0.1%; the mass percentage of acrylonitrile in hydrogenated nitrile rubber is 20%; the vertical dimension of graphene is 1nm and the lateral dimension is 0.5m.
[0065] The preparation method of the rubber sealing material in this embodiment is different from that in Embodiment 1 in that:
[0066] In step S1, the graphene modification reaction temperature is 130° C., and the reaction time is 6 hours; the internal mixer is pre-adjusted to a temperature of 80° C., and the subsequent internal mixing temperature is 130° C., and the mixing time is 10 minutes to prepare a modified rubber mixture;
[0067] In step S2, the mixing temperature of the first stage mixing is 90° C., the mixing time is 8 min, and a first stage mixed rubber is prepared.
[0068] In step S3, the second stage mixing temperature is 55°C, the mixing time is 3 minutes, and the mixture is left to stand for 24 hours, thereby preparing the rubber sealing material of this embodiment.
[0069] Example 4
[0070] The rubber sealing material of this embodiment includes, by mass, 60 parts of fluorosilicone rubber, 40 parts of hydrogenated nitrile rubber, 8 parts of graphene, 0.8 parts of 3-mercaptopropyl triethoxysilane, 35 parts of carbon black N990, 15 parts of silicon dioxide, 1.9 parts of sulfur, 2 parts of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 1.5 parts of trimethylolpropane triacrylate, 3 parts of accelerator NS, 10 parts of liquid nitrile rubber, 2.5 parts of zinc oxide, 1.5 parts of stearic acid, and 3 parts of antioxidant RD. Among them, the molecular weight of fluorosilicone rubber is 500,000, and the molar content of vinyl is 5%; the mass percentage of acrylonitrile in hydrogenated nitrile rubber is 30%; the vertical dimension of graphene is 2nm and the lateral dimension is 1m.
[0071] The preparation method of the rubber sealing material in this embodiment is different from that in Embodiment 1 in that:
[0072] In step S1, the graphene modification reaction temperature is 110° C., and the reaction time is 8 hours; the internal mixer is pre-adjusted to a temperature of 70° C., and the subsequent internal mixing temperature is 140° C., and the mixing time is 6 minutes to prepare a modified rubber mixture;
[0073] In step S2, the mixing temperature of the first stage mixing is 90° C., the mixing time is 9 min, and a first stage mixed rubber is prepared;
[0074] In step S3, the second stage mixing temperature is 60°C, the mixing time is 3 minutes, and the mixture is left to stand for 24 hours, thereby preparing the rubber sealing material of this embodiment.
[0075] Example 5
[0076] The rubber sealing material of this embodiment includes, by mass, 75 parts of fluorosilicone rubber, 25 parts of chloroprene rubber, 6 parts of graphene, 3 parts of 3-mercaptopropyl triethoxysilane, 35 parts of carbon black N550, 25 parts of carbon black N330, 15 parts of silicon dioxide, 2.5 parts of sulfur, 3 parts of diisopropyl peroxide, 1.5 parts of trimethylolpropane triacrylate, 2 parts of accelerator CZ, 20 parts of liquid ethylene propylene rubber, 3 parts of zinc oxide, 1 part of stearic acid, and 22463 parts of antioxidant. Among them, the molecular weight of fluorosilicone rubber is 600,000, and the molar content of vinyl is 0.1%; the vertical size of graphene is 2nm and the lateral size is 1m.
[0077] The preparation method of the rubber sealing material in this embodiment is different from that in Embodiment 1 in that:
[0078] In step S1, the graphene modification reaction temperature is 150° C., and the reaction time is 6 hours; the internal mixer is pre-adjusted to a temperature of 60° C., and the subsequent internal mixing temperature is 150° C., and the mixing time is 5 minutes to prepare a modified rubber mixture;
[0079] In step S2, the mixing temperature of the first stage mixing is 80° C., the mixing time is 5 min, and a first stage mixed rubber is prepared;
[0080] In step S3, the second stage mixing temperature is 70°C, the mixing time is 4 minutes, and the mixture is left to stand for 24 hours, thereby preparing the rubber sealing material of this embodiment.
[0081] Example 6
[0082] The rubber sealing material of this embodiment includes, by mass, 60 parts of fluorosilicone rubber, 40 parts of hydrogenated nitrile rubber, 10 parts of graphene, 1.5 parts of 3-mercaptopropylmethyldimethoxysilane, 35 parts of carbon black N990, 15 parts of silicon dioxide, 1.9 parts of sulfur, 2 parts of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 0.5 parts of trimethylolpropane triacrylate, 4 parts of accelerator NS, 10 parts of liquid fluororubber, 2.5 parts of zinc oxide, 1.5 parts of stearic acid, and 6 parts of antioxidant RD. Among them, the molecular weight of fluorosilicone rubber is 500,000, and the molar content of vinyl is 5%; the mass percentage of acrylonitrile in hydrogenated nitrile rubber is 50%; the vertical dimension of graphene is 3nm and the lateral dimension is 1.5m.
[0083] The preparation method of the rubber sealing material in this embodiment is different from that in Embodiment 1 in that:
[0084] In step S1, the graphene modification reaction temperature is 150° C., and the reaction time is 2 h; the internal mixer is pre-adjusted to a temperature of 80° C., and the subsequent internal mixing temperature is 150° C., and the mixing time is 5 min, to prepare a modified rubber mixture;
[0085] In step S2, the mixing temperature of the first stage mixing is 90° C., the mixing time is 6 min, and a first stage mixed rubber is prepared;
[0086] In step S3, the second stage mixing temperature is 80°C, the mixing time is 4 minutes, and the mixture is left to stand for 24 hours, thereby preparing the rubber sealing material of this embodiment.
[0087] Example 7
[0088] The rubber sealing material of this embodiment includes, by mass, 50 parts of fluorosilicone rubber, 50 parts of nitrile rubber, 2 parts of graphene, 0.1 parts of 3-mercaptopropylmethyldiethoxysilane, 30 parts of carbon black N330, 3 parts of sulfur, 0.5 parts of 1,3-di-tert-butylperoxyisopropylbenzene, 3 parts of triallyl isocyanurate, 1 part of accelerator DM, 5 parts of diisononyl adipate, 2 parts of zinc oxide, 2 parts of stearic acid, and 4 parts of antioxidant 4010NA. Among them, the molecular weight of fluorosilicone rubber is 300,000, and the molar content of vinyl is 0.1%; the mass percentage of acrylonitrile in nitrile rubber is 30%; the vertical size of graphene is 3nm and the lateral size is 2m.
[0089] The preparation method of the rubber sealing material in this embodiment is different from that in Embodiment 1 in that:
[0090] In step S1, the graphene modification reaction temperature is 120° C., and the reaction time is 8 hours; the internal mixer is pre-adjusted to a temperature of 60° C., and the subsequent internal mixing temperature is 130° C., and the mixing time is 7 minutes to prepare a modified rubber mixture;
[0091] In step S2, the mixing temperature of the first stage mixing is 80° C., the mixing time is 5 min, and a first stage mixed rubber is prepared;
[0092] In step S3, the second stage mixing temperature is 80°C, the mixing time is 3 minutes, and the mixture is left to stand for 24 hours, thereby preparing the rubber sealing material of this embodiment.
[0093] Example 8
[0094] The rubber sealing material of this embodiment includes, by mass, 60 parts of fluorosilicone rubber, 40 parts of hydrogenated nitrile rubber, 8 parts of graphene, 1 part of 3-mercaptopropyl triethoxysilane, 35 parts of carbon black N990, 15 parts of silicon dioxide, 0.5 parts of sulfur, 3 parts of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 1.5 parts of trimethylolpropane triacrylate, 8 parts of accelerator NS, 10 parts of liquid ethylene-propylene rubber, 0.5 parts of zinc oxide, 0.5 parts of stearic acid, and 6 parts of antioxidant RD. Among them, the molecular weight of fluorosilicone rubber is 300,000, and the molar content of vinyl is 0.1%; the mass percentage of acrylonitrile in hydrogenated nitrile rubber is 20%; the vertical dimension of graphene is 4nm and the lateral dimension is 2m.
[0095] The preparation method of the rubber sealing material in this embodiment is different from that in Embodiment 1 in that:
[0096] In step S1, the graphene modification reaction temperature is 120° C., and the reaction time is 8 hours; the internal mixer is pre-adjusted to a temperature of 60° C., and the subsequent internal mixing temperature is 130° C., and the mixing time is 7 minutes to prepare a modified rubber mixture;
[0097] In step S2, the mixing temperature of the first stage mixing is 90° C., the mixing time is 8 min, and a first stage mixed rubber is prepared;
[0098] In step S3, the second stage mixing temperature is 80°C, the mixing time is 3 minutes, and the mixture is left to stand for 24 hours, thereby preparing the rubber sealing material of this embodiment.
[0099] Example 9
[0100] The rubber sealing material of this embodiment includes, by mass, 50 parts of fluorosilicone rubber, 50 parts of nitrile rubber, 2 parts of graphene, 1 part of 3-mercaptopropylmethyldiethoxysilane, 30 parts of carbon black N330, 0.5 parts of sulfur, 5 parts of 1,3-di-tert-butylperoxyisopropylbenzene, 1.2 parts of triallyl isocyanurate, 2.5 parts of accelerator TMTM, 5 parts of dioctyl adipate, 1.5 parts of zinc oxide, 2 parts of stearic acid, and 4 parts of antioxidant 4010NA. Among them, the molecular weight of fluorosilicone rubber is 500,000, and the molar content of vinyl is 1%; the mass percentage of acrylonitrile in nitrile rubber is 50%; the vertical size of graphene is 5nm and the lateral size is 5m.
[0101] The preparation method of the rubber sealing material of this embodiment is the same as that of Embodiment 1.
[0102] Example 10
[0103] The rubber sealing material of this embodiment includes, by mass, 80 parts of fluorosilicone rubber, 20 parts of nitrile rubber, 5 parts of graphene, 5 parts of 3-mercaptopropyltrimethoxysilane, 50 parts of carbon black N330, 10 parts of silicon dioxide, 0.5 parts of sulfur, 5.5 parts of diisopropyl peroxide, 1.5 parts of N,N'-m-phenylene bismaleimide, 1.5 parts of accelerator TMTD, 5 parts of diisooctyl sebacate, 3 parts of zinc oxide, 3 parts of stearic acid, and 3 parts of antioxidant RD. Among them, the molecular weight of fluorosilicone rubber is 300,000, and the molar content of vinyl is 1%; the mass percentage of acrylonitrile in nitrile rubber is 20%; the vertical size of graphene is 5nm and the lateral size is 5m.
[0104] The preparation method of the rubber sealing material of this embodiment is the same as that of Example 2.
[0105] Embodiment 11
[0106] The rubber sealing material of this embodiment includes, by mass, 70 parts of fluorosilicone rubber, 30 parts of hydrogenated nitrile rubber, 3 parts of graphene, 5 parts of 3-mercaptopropyltrimethoxysilane, 40 parts of carbon black N660, 10 parts of silicon dioxide, 0.8 parts of sulfur, 5 parts of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 2 parts of trimethylolpropane triacrylate, 3.5 parts of accelerator M, 15 parts of diisooctyl sebacate, 2.5 parts of zinc oxide, 2.8 parts of stearic acid, and 2 parts of antioxidant MB. Among them, the molecular weight of fluorosilicone rubber is 500,000, and the molar content of vinyl is 0.1%; the mass percentage of acrylonitrile in hydrogenated nitrile rubber is 20%; the vertical dimension of graphene is 5nm and the lateral dimension is 5m.
[0107] The preparation method of the rubber sealing material of this embodiment is the same as that of Example 3.
[0108] Example 12
[0109] The difference between this embodiment and embodiment 1 is that the method for preparing the rubber sealing material does not include a step of modifying graphene.
[0110] Example 13
[0111] The difference between this embodiment and embodiment 1 is that the raw material of the rubber sealing material does not contain a modifier, and the preparation method thereof does not include a step of modifying graphene.
[0112] Embodiment 14
[0113] The difference between this embodiment and embodiment 2 is that the raw material of the rubber sealing material does not contain a modifier, and the preparation method thereof does not include a step of modifying graphene.
[0114] Embodiment 15
[0115] The difference between this embodiment and embodiment 3 is that the raw material of the rubber sealing material does not contain a modifier, and the preparation method thereof does not include a step of modifying graphene.
[0116] Comparative Example 1
[0117] The difference between this embodiment and embodiment 1 is that the raw material of the rubber sealing material does not contain graphene, and the preparation method thereof does not include a step of modifying the graphene.
[0118] Comparative Example 2
[0119] The difference between this embodiment and embodiment 2 is that the raw material of the rubber sealing material does not contain graphene, and the preparation method thereof does not include a step of modifying the graphene.
[0120] Comparative Example 3
[0121] The difference between this embodiment and embodiment 3 is that the raw material of the rubber sealing material does not contain graphene, and the preparation method thereof does not include a step of modifying the graphene.
[0122] The performance comparison of the samples in the above examples and comparative examples is shown in Table 1 below.
[0123] Table 1
[0124]
[0125]
[0126] From Table 1 above, we can see that:
[0127] (1) The rubber sealing material of the present invention has a tensile strength of 5.0 to 16.8 MPa, an elongation at break of 170% to 349%, a low-temperature brittle temperature of -65°C to -40°C, a hardness change range of -12.0 to +1.1 after oil immersion, and a volume change range of +2.3 to 12.7 after oil immersion, showing excellent mechanical properties, low-temperature resistance and oil resistance;
[0128] (2) Compared with Examples 1 to 11, Comparative Examples 1 to 3 do not contain graphene. From the performance data of the samples, it can be seen that the mechanical properties, low temperature resistance and oil resistance of Comparative Examples 1 to 3 are significantly reduced. It can be seen that the introduction of graphene into the rubber matrix of the present invention can improve the barrier properties of the rubber material and significantly improve the overall mechanical strength, low temperature resistance and oil resistance of the rubber sealing material;
[0129] (3) Compared with Examples 1 to 11, Examples 12 to 15 did not undergo modification treatment on the graphene. From the performance data of the samples, it can be seen that the mechanical properties, low temperature resistance and oil resistance of Examples 12 to 15 were significantly reduced. It can be seen that the modified graphene has better dispersibility in the rubber matrix, giving the rubber sealing material better mechanical properties, low temperature resistance and oil resistance.
[0130] The above are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are included in the scope of the claims of the present invention to be approved.
Claims
1. A rubber sealing material, characterized in that: The raw materials are comprised of the following, in parts by mass: 50-80 parts of fluorosilicone rubber, 20-50 parts of polar rubber, 2-10 parts of graphene, 30-60 parts of filler, 3-20 parts of vulcanizing agent and 7.1-31 parts of auxiliary agent.
2. The rubber sealing material according to claim 1, characterized in that: The fluorosilicone rubber contains 0.1-5% of vinyl in molar mass, and the molecular weight of the fluorosilicone rubber is 300,000-600,000.
3. The rubber sealing material according to claim 1, characterized in that: The polar rubber is one or more of nitrile rubber with an acrylonitrile mass percentage of 20-50%, hydrogenated nitrile rubber with an acrylonitrile mass percentage of 20-40%, and chloroprene rubber.
4. The rubber sealing material according to claim 1, characterized in that: The vertical thickness of the graphene is 1-5 nm, and the lateral thickness is 0.5-5 nm.
5. The rubber sealing material according to claim 1, characterized in that: The filler is one or more of carbon black and silicon dioxide.
6. The rubber sealing material according to claim 1, characterized in that: The filler is in a spherical shape and is embedded with the graphene sheet structure to form a staggered grid structure.
7. The rubber sealing material according to claim 1, characterized in that: The vulcanization treatment agent includes the following components in parts by mass: 0.5-3 parts of zinc oxide, 0.5-3 parts of stearic acid, 0.5-3 parts of co-vulcanizing agent, 0.5-5 parts of vulcanization accelerator, 0.5-3 parts of sulfur vulcanizing agent and 0.5-3 parts of peroxide vulcanizing agent.
8. The rubber sealing material according to claim 7, characterized in that: The auxiliary vulcanizing agent is one or more of triallyl isocyanurate, N,N'-m-phenylene bismaleimide and trimethylolpropane triacrylate.
9. The rubber sealing material according to claim 7, characterized in that: The vulcanization accelerator is one or more of accelerator TMTM, accelerator TMTD, accelerator M, accelerator DM, accelerator CZ, and accelerator NS.
10. The rubber sealing material according to claim 7, characterized in that: The peroxide curing agent is one or more of 1,3-di-tert-butylperoxyisopropylbenzene, diisopropylbenzene peroxide, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.
11. The rubber sealing material according to claim 1, characterized in that: The auxiliary agent includes the following components in parts by mass: 5 to 20 parts of low temperature resistant plasticizer, 0.1 to 5 parts of modifier and 2 to 6 parts of antioxidant.
12. The rubber sealing material according to claim 11, characterized in that: The low temperature resistant plasticizer is one or more of dioctyl adipate, diisooctyl sebacate, diisononyl adipate, liquid nitrile rubber, liquid ethylene propylene rubber, and liquid fluorosilicone rubber.
13. The rubber sealing material according to claim 11, characterized in that: The modifier is one or more of 3-mercaptopropylmethyldiethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane.
14. The rubber sealing material according to claim 11, characterized in that: The antioxidant is one or more of antioxidant RD, antioxidant 4010NA, antioxidant 2246, and antioxidant MB.
15. A method for preparing a rubber sealing material according to any one of claims 1 to 14, characterized in that: The following steps are involved: Rubber matrix mixing: mixing fluorosilicone rubber, polar rubber and graphene at 120-150° C. for 5-10 minutes to obtain a rubber matrix mixed rubber; One-stage mixing: adding fillers and additives to the rubber matrix mixed rubber, mixing at 80-100° C. for 5-10 minutes to obtain a one-stage mixed rubber; Second stage mixing: adding a vulcanizing agent to the first stage mixed rubber, and performing second stage mixing at 50 to 80° C. for 3 to 5 minutes to prepare the rubber sealing material.
16. The method for preparing a rubber sealing material according to claim 15, characterized in that: The rubber matrix further comprises: Placing graphene powder in a dispersion, adding a modifier, carrying out a modification reaction at 100 to 150° C. for 2 to 10 hours, and obtaining a modified graphene wet powder after suction filtration; The graphene in the rubber matrix mixing process is modified graphene.
17. The method for preparing a rubber sealing material according to claim 16, characterized in that: The mass content of the modifier is 0.1 to 2 times that of the graphene.